Numerical simulations of the wind flow and ozone formation during the Heilbronn ozone experiment. (4th August 2014) - Moussiopoulos, N.; Sahm, P.; Vogele, T.; Kunz, R.
The Heilbronn ozone experiment was aimed at investigating the impact of short–term local–scale interventions on peak ozone levels during summer smog periods. The measures taken were estimated to lead to considerable reductions of road traffic emissions, but to only smaller reductions of industrial emissions. Model simulations with the European Zooming Model (EZM) were performed for assessing the effectiveness of the emission reduction interventions. The evaluation of both simulation results and extensive meteorological and air quality measurements carried out during the experiment reveals that the interventions lead to air quality improvements with regard to the primary pollutant concentrations but to only minor changes in peak ozone levels. The main conclusion from the Heilbronn ozone experiment is that concerted large–scale interventions to the primary pollutant sources are needed for decisive reductions of peak ozone concentrations in Central Europe.